Pendidikan Karakter: Komparasi TK Islam dan TK Umum di SD Al-Kautsar Bandar Lampung - Sagala, Rumadani; Romlah , Romlah; Putri Amanah, Adinda (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2020)
The purpose of this study was to identify the various types of student delinquency and the causes and understand how to deal with student delinquency. The method used is qualitative research. This research was conducted at SD AL-Kautsar Bandar Lampung. Data obtained from interviews with school principals and teacher educators and questionnaires distributed to students. Data were analyzed using the following steps: data reduction, data display and conclusion/verification. Based on the results of research in the field, the authors conclude that character education at SD Al-Kautsar Bandar Lampung is very good in terms of teaching and practice. Character development in schools is pursued through several ways including learning activities in the classroom and outside the classroom with qualified teachers who are believed to be able to build the character of their students, as well as cooperation from parents of students in cultivating good character at home.